Port State Control: Perceptions on conflicts - Falk, Andreas (My University, 2016)
Port State Control has become an important aspect in the enforcement of international regulations. The practice of Port State Control was implemented in recognition to the fact that certain flag states were unable or unwilling to enforce international rules and standards on vessel in their register. Since the start of the regional cooperation under Paris Memorandum of Understanding in Europe has the regime of Paris MoU seen much development? The means of assuring that foreign vessels are in compliance with international regulations range from detaining substandard vessels to using information systems to raise awareness with the general public and also as a warning system for substandard vessels. Through the Paris MoU website can any person access information on the results of an inspection of a vessel, which has been inspected by a member state of Paris MoU. This information has an impact on a shipping company commercial position, as charterers can easily access the inspection record on any vessel. With the high stakes following an inspection is it not unlikely that conflicts can emerged between the two parties, the authority and the ship owner? This thesis explores the different perceptions on conflicts around Port State Control inspections. The available Appeal procedures for ship owners in the member states and Paris MoU have been mapped to examine the means for a ship owner to raise concerns in case a mistake has been made in an inspection. The findings show a high difference on the perceptions. The authorities which participated in the research indicated no conflicts, while the participating shipping company and shipping association gave the opposite view and an indication of unreported cases are common. Plausible causes for conflicts has been identified as interpretation of regulations and improperly trained crews and Port State Control Officers. Following these findings was the development of Paris MoU and the STCW code examined. The examinations showed that Paris MoU has developed vastly in recent time while the STCW code has not seen any major developments in the competences connected to ensuring compliance with legislative requirements. Recommendations to ship owners has been identified which includes internal education and utilization of coming Paris MoU publications. The final findings of this thesis points to that further research in the area can bring further light on the subject, for which the available previous research has been severely limited.
Keywords: Transport; Hållbar utveckling; Transportteknik och logistik; Transport; Sustainable Development; Transport Systems and Logistics